2018
DOI: 10.3389/fendo.2018.00437
|View full text |Cite
|
Sign up to set email alerts
|

KISS1/KISS1R in Cancer: Friend or Foe?

Abstract: The KISS1 gene encodes KISS1, a protein that is rapidly processed in serum into smaller but biologically active peptides called kisspeptins (KPs). KISS1 and the KPs signal via the G-protein coupled receptor KISS1R. While KISS1 and KPs are recognized as potent positive regulators of the reproductive neuroendocrine axis in mammals, the first reported role for KISS1 was that of metastasis suppression in melanoma. Since then, it has become apparent that KISS1, KPs, and KISS1R regulate the development and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 69 publications
(103 reference statements)
1
47
0
Order By: Relevance
“…In addition to the classic prognostic factors, molecular expression patterns provide more predictive information for clinical outcomes of CRC patients . For example, KISS1 and KISS1R, a new pair of metastasis suppressors in cancers, have been associated with CRC prognosis; however, conflicting results have been reported . The present study demonstrated that low KISS1 expression indicated poorer overall survival in CRC patients.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In addition to the classic prognostic factors, molecular expression patterns provide more predictive information for clinical outcomes of CRC patients . For example, KISS1 and KISS1R, a new pair of metastasis suppressors in cancers, have been associated with CRC prognosis; however, conflicting results have been reported . The present study demonstrated that low KISS1 expression indicated poorer overall survival in CRC patients.…”
Section: Discussionmentioning
confidence: 54%
“…For example, in colorectal, bladder and renal cell carcinoma, KISS1 expression was decreased, and this was associated with lower survival rates and increases in metastasis. At the same time, in breast cancer stem cells, KISS1/KISS1R expression was upregulated, appeared to promote tumour growth and metastasis, and was associated with poor outcome . As Kostakis et al have previously proposed, Kisspeptins might possess tumour promotion properties or they might be activated in advanced disease stages as a defensive response against metastasis.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations